Three-dimensional ultrasound evaluation of tongue posture and its impact on articulation disorders in preschool children with anterior open bite - Lah Kravanja, Sanda (Radiology and oncology (Ljubljana), 2018)
Background. Tongue posture plays an important role in the etiology of anterior open bite (AOB) and articulation disorders, and is crucial for AOB treatment planning and posttreatment stability. Clinical assessment of tongue posture in children is unreliable due to anatomical limitations. The aim of the study was to present functional diagnostics using three-dimensional ultrasound (3DUS) assessment of resting tongue posture in comparison to clinical assessment, and the associations between the improper tongue posture, otorhinolaryngological characteristics, and articulation disorders in preschool children with AOB. Patients and methods. A cross-sectional study included 446 children, aged 3-7 years, 236 boys and 210 girls, ex- amined by an orthodontist to detect the prevalence of AOB. The AOB was present in 32 children. The control group consisted of 43 children randomly selected from the participants with normocclusion. An orthodontist, an ear, nose and throat (ENT) specialist and a speech therapist assessed orofacial and ENT conditions, oral habits, and articulation disorders in the AOB group and control group. Tongue posture was also assessed by an experienced radiologist, us- ing 3DUS. The 3DUS assessment of tongue posture was compared to the clinical assessment of orthodontist and ENT specialist. Results. The prevalence of AOB was 7.2%. The AOB group and the control group significantly differed regarding improper tongue posture (p < 0.001), and articulation disorders (p < 0.001). In children without articulation disorders from both groups, the improper tongue posture occured less frequently than in children with articulation disorders (p < 0.001). After age adjustment, a statistical regression model showed that the children with the improper tongue posture had higher odds ratios for the presence of AOB (OR 14.63; p < 0.001) than the others. When articulation disor- ders were included in the model, these odds ratios for the AOB became insignificant (p = 0.177). There was a strong association between the improper tongue posture and articulation disorders (p = 0.002). The 3DUS detected the high- est number of children with improper resting tongue posture, though there was no significant difference between the 3DUS and clinical assessments done by orthodontist and ENT specialist. Conclusions. The 3DUS has proved to be an objective, non-invasive, radiation free method for the assessment of tongue posture and could become an important tool in functional diagnostics and early rehabilitation in preschool children with speech irregularities and irregular tongue posture and malocclusion in order to enable optimal condi- tions for articulation development.
Keywords: anterior open bite; drža jezika; prednji odprti ugriz; three-dimensional ultrasound; tongue posture; tridimenzionalni ultrazvok